Sustainability-oriented innovation system and economic stability of the innovative countries - Manzoor, Faiza; Wei, Longbao; Subhan, Qazi Abdul; Siraj, Mahwish (Frontiers in Public Health, 2023)
The novel coronavirus 19 has created a challenging situation for developed as well as developing countries to sustain economic stability. There are a lot of controversies for policymakers to formulate an effective policy for reviving economic stability and minimizing the economic effects of this pandemic. The present study focuses on the internal mechanism of the Sustainability Oriented Innovation System and its subsequent effects on economic stability in most innovative economies. For empirical analysis of the most innovative countries (12 countries) high-income, middle-income, low-income, and lower-middle-income countries have been selected. SOIS has been represented through the innovation input index and innovation output index. Economic stability is measured through the GDP growth rate of respective countries. A set of panel data have developed for the period of 11 years; 2011-2021. The study's empirical results show that innovation is the main force of economic stability. Empirical outcomes are important to policymakers to promote, stimulate and support economic stability through their strategies.